How the driving behaviors and customer handling of public transportation operators have been impacted by the COVID-19 pandemic in Addis Ababa, Ethiopia: the perspective of protection motivation theory? - Tareke, Kassa Moges (Frontiers in Sustainable Cities, 2023)
The COVID-19 pandemic has had an impact on every aspect of human life and economic sectors such as transportation operations around the world. This paper tries to investigate how COVID-19 pandemic factors and subsequent government response measures influenced the driving and customer handling behaviors of urban public transportation operators in Hawassa and Addis Ababa, Ethiopia. To that end, a framework of mixed research, pre/post study design, and protection motivation theory (PMT) was used to guide the development, quantification, and analysis of the causal relationships of pandemic-related constructs on driving and customer handling behaviors. The examined driving behavior variables included harsh speeding, harsh braking, and drink-drive events concerning the time period before and during the COVID-19 pandemic outbreak. Customer handling was also operationalized in terms of the level of friendly handling and care provided to customers. As a result, primary data were collected through transport surveys on 132 randomly selected public transit operators, including city buses, midsize buses, minibuses, bajajs, and light rail transits. Furthermore, contingency indexes, likert scales, and binary logistic regression models were used to estimate and predict the most significant factors that affected driving and customer handling behavior. Findings showed that the new COVID-19 pandemic and response measure-related factors were the most significant factors impacting driving behavior during the pandemic. Driving frequencies and intentions, as well as driving decisions or choices, were significantly influenced and reduced. Due to the pandemic-related factors, harsh driving behaviors such as harsh speeding and braking became more frequent during the pandemic compared to the pre-COVID period. Additionally, the correlation between harsh driving behavior and other factors, mainly trip distance traveled, driving during risky nighttime hours, and driving requests, was significant. Furthermore, due to the impacts of COVID-19, government measures, and changes in driving behavior, customer handling and care behaviors were predominantly unfriendly. Findings revealed that the performance of PMT was relevant and could inform and guide studies to understand such an impact analysis. Thus, policymakers must learn from the harsh lessons of COVID-19 and make bold investments in preparedness, prevention, and response, including pandemic-sensitive strategies and customer-oriented strategies.